ANTIFUNGAL EFFICACY OF AQUEOUS EXTRACTS OF NEEM CAKE, KARANJ CAKE AND VERMICOMPOST AGAINST SOME PHYTOPATHOGENIC FUNGI - ANJALI KUMARI, RITESH KUMAR, SUDARSHAN MAURYA, JAIPAL SINGH CHOUDHARY AND S. KUMAR, (The Bioscan, 2013)
Several agro-based waste and byproducts are known and cited to play an important role in the management of plant diseases in ancient texts. They act directly or indirectly on plant pathogens to inhibit the growth and multiplication or by inducing resistance in crop plants. In the present experiments, aqueous extracts of neem cake, karanj cake and vermicompost were tested against some important phytopathogenic fungi viz., Helminthosporium pennisetti, Curvularia lunata and Colletotrichum gloeosporioides f. sp. mangiferae for their antifungal activities. H. pennisetti was found to be most sensitive one followed by C. gloeosporioides f. sp. mangiferae and C. lunata against all the tested drugs. Against C. gloeosporioides f. sp. mangiferae, aqueous extract of karanj cake was most effective where GI50 was found to be 0.41% drug concentration followed by neem cake (0.46%) and vermicompost (0.86%). In case of C. lunata and H. pennisetti, neem cake extract was most effective with GI50 value of 0.27% and 0.11% respectively. The GI50 values noted for C. lunata with extracts of karanj cake (0.70%), vermicompost (0.88%) and for H. pennisetti were (0.20%) and (0.22%) respectively.